Hylocereus polyrhizus Peel Extract Increase Testosteron Levels of Balb/C Mice (Mus musculus) Exposed Lead Acetate - Reny I’tishom; Evy Wulandari; Sri Agus Sudjarwo (Universitas Airlangga, 2020)
Lead is a heavy metal, the main polluting material in the environment, which comes from gasoline, batteries, paint, pipes, soil, cosmetics, household appliances, and decorations. Lead is a free radical causing oxidative stress. Lead can accumulate in the body due to its slow elimination process. Lead increases oxidative stress by forming reactive oxygen species (ROS) such as superoxide ion (O2-), hydroxil radical (OH-), and nitric oxide (NO), and direct suppression of antioxidant reserves such as Superoxide Dismutase (SOD), Catalase, and Glutathione Peroxide (GPx). Hylocereus polyrhizus peel is a natural antioxidant that can overcome the toxic effects of lead. The aim of this study was to analyze the treatment of Hylocereus polyrhizus peel extract orally once in a day for 40 days to increase testosteron levels of Balb/C mice (Mus musculus) exposed to lead acetate. The type of this study was true experimental study with Post Test Only Control Group design. Forty mice aged 8-10 weeks and the range of the body weight 30-40 grams were divided into 5 groups (each group of 8 mice). K- group was the control group without lead acetate and Hylocereus polyrhizus peel extract. K+, P1, P2 and P3 group was given 100 mg/kgBW lead acetate orally on the 1st day until day 14th. P1, P2 and P3 group was continued by giving Hylocereus polyrhizus peel extract orally on the 15th day until 39th day. P1 with dose 250 mg/KgBW, P2 with dose 500 mg/KgBW, and P3 with dose 1000 mg/KgBW. The results showed significant differences in testosterone levels between the K+ groups with P1 and P2. The conclusion of this study is Hylocereus polyrhizus peel extract can increase the testosteron levels of mice exposed to acetate lead.